Portable Modular Pool Prototyping for Military Training and Testing in Remote Environment - Yaman, Rostam; Ismail, Farrah Zuhaira; Ab Aziz, Lt Kol Ali Zakafri; Muhamad Ariff, Nor Rima; Kaliwon, Julaida; Aris, Nurul Nabilah; Ahmad, Noraini; Nanta, Piyarat (International Journal of Sustainable Construction Engineering and Technology, 2023)
Military training and periodical assessment are essential in preparing a well-built soldier physically and mentally for the Malaysian Army Forces. One of them is the water survival training test. The test consists of a series of aquatic tasks conducted in a remote area. As a matter of fact, it requires a water-pool facility which is durable and portable. Therefore, this research aims to design and prototype a modular portable swimming pool for floating exercises and assessment for military personnel. The study is conducted in partnership with the Royal Army Engineers Regiment, with the objectives being to design, simulate, prototype, and build the modular portable swimming pool for military uses. The study output was tested, evaluated, and appraised on the swimming pool workability on site. The methodology is divided into 4 phases; (i) Content Studies and Design Profiling, (ii) Digital Prototyping, Evaluation and Testing, (iii) Physical Prototyping - Materials and Method; and (iv) Application and Measurement. The study seeks to maximise the training of military personnel and reduce the transportation time and resource costs of building a permanent pool by placing it with a modular portable swimming pool, which is more cost-efficient and user-friendly. The findings of Phase 1 prototyping required improvement on design structure where it indicated disadvantages in sustaining water volume ability at targeted level due to structural integrity. Upon improvement of Phase 2 prototyping using metal with bracing frame the pool are able to sustain the desired water volume at 5200 l3. Moreover, this study, also responds to the approaches of the Sustainable Development Goals (SDGs) 9, 16 and 17 towards harmonizing and interconnecting the three core elements of sustainability, economic growth, social inclusion, and environmental protection for human well-being.